2022
DOI: 10.1111/jocs.16328
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve biologic protheses: A cohort comparison of premature valve failure

Abstract: Background Recent reports suggest an increased rate of early structural valve degeneration (SVD) in the Trifecta bioprosthesis (Abbott Cardiovascular). We sought to compare the intermediate‐term outcomes of the Magna (Edwards Life Sciences) and Trifecta valves. Methods All surgical aortic valve replacements (SAVRs) with Trifecta or Magna/Magna Ease bioprostheses at an academic medical center were extracted from an institutional database. Patients who survived until after discharge (2011–2019) were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, comparing SVD rates from different studies is challenging because of differing SVD definitions and cohort ages. Freedom from SVD with the Trifecta valve was reported to be 98.7% and 93.3% at 5 and 8 years, respectively, 13 although a recent study demonstrated an increased risk of valve failure in the Trifecta valve compared with the Magna Ease valve at 48 months 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparing SVD rates from different studies is challenging because of differing SVD definitions and cohort ages. Freedom from SVD with the Trifecta valve was reported to be 98.7% and 93.3% at 5 and 8 years, respectively, 13 although a recent study demonstrated an increased risk of valve failure in the Trifecta valve compared with the Magna Ease valve at 48 months 16 …”
Section: Discussionmentioning
confidence: 99%
“…Freedom from SVD with the Trifecta valve was reported to be 98.7% and 93.3% at 5 and 8 years, respectively, 13 although a recent study demonstrated an increased risk of valve failure in the Trifecta valve compared with the Magna Ease valve at 48 months. 16 Freedom from reintervention due to SVD was 99.1% (95% CI: 97.9, 100.0) at 5 years and 93.6% (95% CI: 89.3, 97.8) at 8 years.…”
Section: Valve Durabilitymentioning
confidence: 93%
“…Freedom from SVD with the Trifecta valve was reported to be 98.7% and 93.3% at 5 and 8 years, respectively, [15] although a recent study demonstrated increased risk of valve failure in the Trifecta valve compared with the Magna Ease valve at 48 months. [18] Freedom from reintervention due to SVD was 99.1% (95% CI 97.9, 100.0) at 5 years and 93.6% (95% CI 89.3, 97.8) at 8 years. Rates reported for the Trifecta valve were 97.3% (95% CI 94.7, 98.6) at 6 years.…”
Section: Valve Durabilitymentioning
confidence: 93%
“…[14][15][16] The Freestyle valve (Medtronic, Dublin, Ireland) showed similar rates of 10-year survival to Magna Ease in a retrospective cohort analysis. [17,18] In another multivariable retrospective analysis, the Mitroflow valve (LivaNova, London, UK) was associated with a higher risk of mortality compared with the Magna Ease valve at 5 years (hazard ratio 1.57 [95% CI 1.17, 2.11], p<0.01). [19] Thromboembolic events, bleeding, and endocarditis…”
Section: Survivalmentioning
confidence: 99%
“…In this issue of the journal, Yount et al consider two bioprosthetic aortic valves: the Trifecta valve (Abbott Cardiovascular) and the Magna/Magna Ease valve (Edwards Life Sciences). 13 They use retrospective institutional data to compare the rates of valve failure for these commercially available bioprosthetic heart valves. The study is clinically relevant as it aims to build on recent evidence suggesting Trifecta valves may be susceptible to early failure.…”
mentioning
confidence: 99%